Medical Errors Disclosure: Is It Good or Bad? - Amirashkan Nasiripour; Pouran Raeissi; Mehrnoosh Jafari (Baqiyatallah University of Medical Sciences, 2018)
Background: In the treatment and health process, there are a lot of dangers to patients, and the increased number of medical errors is one of the most important circumstances of this process. Objective: The present research purposed to decrease medical errors through disclosure of them in hospitals of Tehran University of Medical Sciences. Methods: This qualitative-quantitative study included a population of 232 individuals, selected through targeted non-random selection, who were somehow connected with medical errors made in hospitals affiliated with Tehran University of Medical Sciences. The triangulation technique was utilized to collect data. Data was analyzed using the factor analysis technique. After the effective factors were determined, their internal correlation was determined through regression correlation. Results: Disclosure is made up of organizational culture, the factors related to the patient, the factors related to the presenter, the factors involved in the error, structural factors, and disclosure situation indexes, and is an effective factor in managing the medical errors in hospitals of Tehran University of Medical Sciences. Disclosure increases the immunity of patients. Conclusion: Disclosure is an effective factor in managing the medical errors that occur at hospitals affiliated with Tehran University of Medical Sciences. It is essential that managers identify the effective factors in disclosure and take steps to apply a suitable disclosure system to decrease errors.